PHYSICAL AND ORGANOLEPTIC CHARACTERISTICS OF MILK YOGHOURT COW WITH ADDITION LEAF Pandanus FRAGRANT (Pandanus) Amaryllifolius) - Muh. Afdanul Irham; Syamsududdin; Muhammad Yunus; Lili Suryani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Yogurt is a fermented milk product with high nutritional value and is popular with the public. The addition of pandan leaf extract (Pandanus amaryllifolius Roxb.) can enhance the flavor and provide a natural aroma and color to yogurt. This study aims to determine the effect of adding pandan leaf extract on the physical and organoleptic characteristics of yogurt and to improve the knowledge, skills, and attitudes of Women Farmers Groups (KWT) through extension activities. The study used a Completely Randomized Design (CRD) with four treatments: P0 (without the addition of pandan leaf extract), P1 (10%), P2 (13%), and P3 (16%). The parameters observed included color, taste, aroma, and texture through organoleptic tests. The data were analyzed using analysis of variance (ANOVA), while the effectiveness of the extension was evaluated through pre-test and post-test on 25 members of the Bunga Mawar Women Farmers Group (KWT) in Timbuseng Village, Pattallassang District, Gowa Regency. The results showed that the addition of fragrant pandan leaf extract had a very significant effect (P<0.01) on the physical and organoleptic characteristics of yogurt. Treatment P0 produced the highest scores in color (4.00), taste (3.07), and aroma (2.93), while the best texture was obtained in treatment P2 (3.53). The addition of fragrant pandan leaf extract in high concentrations caused a change in color to a greener color, decreased acidity levels, affected the distinctive aroma of yogurt, and decreased texture stability at the highest concentration. The results of the extension evaluation showed an increase in knowledge from 65.8% to 93%, skills from 50.2% to 81.8%, and attitudes from 62.6% to 84.4%, with an extension effectiveness rate of 66.3%, which is considered effective.